Analisis Efektivitas Penggunaan Sistem Informasi Dalam Mendukung Aktivitas Pembelajaran - Jamariani Jamariani; Alfi Amalia (Forum Kerjasama Pendidikan Tinggi (FKPT), 2026)
This study aims to analyze the effectiveness of using a Learning Management System (LMS), specifically Google Classroom, along with the school’s internal Academic Information System, in supporting learning activities at Darul Mahdiyah Private School, Thailand. A qualitative descriptive approach was employed through observations, interviews, and document analysis involving school administrators, teachers, and students. The findings indicate that the use of the LMS at the upper secondary level improves the organization of learning schedules, material distribution, assignment submission, and attendance recording, while also shifting teacher–student interaction toward more flexible and asynchronous communication. In contrast, learning activities at the primary and lower secondary levels remain predominantly manual. The study also reveals a dual-adaptation pattern, in which teachers combine digital and manual systems as a transitional strategy due to varying levels of technological literacy, highlighting that system effectiveness is influenced not only by technological availability but also by human resource readiness and institutional support.